STRATEGI MENINGKATKAN PENJUALAN MAKANAN MELALUI ANALISIS MENU ENGINEERING DI DOME GARDEN CAFE - I Kadek Surya Andika Jaya; Rimalinda Lukitasari; Luh Sri Damayanti (Jurusan Pariwisata Politeknik Negeri Kupang, 2022)
The principle that sales must provide significant profits needs to be put forward so that business activities can develop properly. Food sales that are not selling well for a long time need to be overcomed with several important steps to strategize. This study aims to develop a strategy to increase food sales at Dome Garden Café. The method used was descriptive qualitative by applying menu engineering analysis and product life cycle theory to develop a strategy to increase food sales. Data were collected through interviews, observation and documentation studies. The results of this study indicate that there are 29% stars category menu, 10% puzzles category, 29% plowhorses category, and 31% dogs category. From the results of the menu engineering analysis, a strategy for the Dome Garden Café was developed based on the product life cycle theory, namely; 1) modification of food recipes, 2) rapid skimming strategy, 3) suggestive selling techniques, 4) menu design, 5) promotion through social media. This research is expected to contribute to the Dome Garden Café and the hospitality industry in general in the utilization of menu engineering to maximize food sales.